Asuhan Keperawatan Anak Pada Pasien Dengan Gastroentritis Akut Di Ruang Marwa Rumah Sakit Aisyiyah Pariaman Tahun 2026 - Atisa Endefi; Prima Yoselina; Reska Handayani; Erpita Yanti (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Acute Gastroenteritis (GAE) is a major health problem in children that contributes to high morbidity and mortality rates. Globally, there are approximately 1.7 billion cases per year, with approximately 443,832 deaths in children aged <5 years. In Indonesia, the prevalence of GEA reaches 60–80% in children, while in the Marwa Room of Aisyiyah Pariaman Hospital, cases increased from 42 cases (2023), 60 cases (2024), to 61 cases (2025) and ranks second most common disease. This study aims to describe nursing care for children with GEA through the stages of assessment, diagnosis, intervention, implementation, and evaluation. The method used is a case study on An. E on February 14-18, 2026 in the Marwa Room of Aisyiyah Pariaman Hospital. The results of the study showed nursing problems in the form of diarrhea, hypovolemia, hyperthermia, and nutritional deficits. Interventions include monitoring vital signs, administering fluids, monitoring intake-output, and family education. Evaluation showed a decrease in diarrhea frequency, normal body temperature, and improved hydration status. Parents are advised to administer oral rehydration salts promptly, maintain hand hygiene, ensure food hygiene, and recognize signs of dehydration such as dry mouth and lethargy. Healthcare workers need to increase family education to prevent complications of GEA.